2017
DOI: 10.1002/2016gc006728
|View full text |Cite
|
Sign up to set email alerts
|

Multianalytical provenance analysis of Eastern Ross Sea LGM till sediments (Antarctica): Petrography, geochronology, and thermochronology detrital data

Abstract: In order to reveal provenance of detrital sediments supplied by West Antarctic Ice Sheet (WAIS), 19 glaciomarine cores of Last Glacial Maximum age were analyzed from Eastern Ross Sea and Sulzberger Bay. Analytical techniques included petrographic analysis of gravel‐sized clasts, geochronology (zircon U‐Pb: Zrn‐UPb) and thermochronology (apatite fission track: AFT) of sand‐sized fractions. Petrographic analysis revealed a similarity with the lithologies presently exposed in western Marie Byrd Land (MBL), with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 83 publications
(235 reference statements)
1
26
0
Order By: Relevance
“…Climate snapshots near magnetic reversals will be targeted (e.g., the M2 glacial in Figure F4) because these events can be traced to more continuous records from the continental rise (Site U1524) and global sea level records. Sediment provenance studies (clast/sand petrology, mineral thermochronology, and radiogenic isotope analysis) at Sites U1521 and U1522 will enable understanding of the changes in the origin of sediments (e.g., local ice caps versus ice sheet expansion and provenance from East versus West Antarctic sources) ( Figure F7) (Licht et al, 2005(Licht et al, , 2014Talarico et al, 2012;Cook et al, 2013;Perotti et al, 2017;Simões Pereira et al, 2018). As with all objectives, data integration with modeling studies will be undertaken ( Figure F4) (Golledge et al, 2012;Wilson et al, 2013;DeConto and Pollard, 2016;Gasson et al, 2016;Colleoni et al, 2018b).…”
Section: Scientific Objectivesmentioning
confidence: 99%
“…Climate snapshots near magnetic reversals will be targeted (e.g., the M2 glacial in Figure F4) because these events can be traced to more continuous records from the continental rise (Site U1524) and global sea level records. Sediment provenance studies (clast/sand petrology, mineral thermochronology, and radiogenic isotope analysis) at Sites U1521 and U1522 will enable understanding of the changes in the origin of sediments (e.g., local ice caps versus ice sheet expansion and provenance from East versus West Antarctic sources) ( Figure F7) (Licht et al, 2005(Licht et al, , 2014Talarico et al, 2012;Cook et al, 2013;Perotti et al, 2017;Simões Pereira et al, 2018). As with all objectives, data integration with modeling studies will be undertaken ( Figure F4) (Golledge et al, 2012;Wilson et al, 2013;DeConto and Pollard, 2016;Gasson et al, 2016;Colleoni et al, 2018b).…”
Section: Scientific Objectivesmentioning
confidence: 99%
“…Such young grains are also present in data sets detected on offshore drill holes such as CIROS‐2 and ANDRILL and were interpreted as related to the widespread Cenozoic volcanic event in the WRS (Zattin et al, 2012). On the contrary, these ages are not present in the fission track detrital distributions in the ERS (Perotti et al, 2017) and in the U‐Pb detrital zircon signature of West Antarctic sites (Licht et al, 2014). Actually, some volcanic centers exist in West Antarctica, but their contribution to the detritus that is flowing into the eastern Ross Sea is very minor (Anderson et al, 1992; Licht et al, 2005; Perotti et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Marie Byrd Land is one of the major crustal blocks forming the West Antarctica. Its western portion is situated today adjacent to the Ross Sea ( Figure 2) (Spiegel et al, 2016), and it is largely covered by the WAIS and mostly grounded below sea level (Licht et al, 2005) although there the best exposed rock outcrops in West Antarctica can be found (Perotti et al, 2017).…”
Section: The Geology Of West Antarcticamentioning
confidence: 99%
See 2 more Smart Citations